Nutritional parameters of exotic and native forage species of Itajaí Valley, Santa Catarina State, Brazil - Deschamps, Francisco Carlos; Tcacenco, Fernando Adami (Pesquisa Agropecuaria Brasileira, 2000)
In order to improve the quality and availability of forages in Itajaí Valley, Santa Catarina State, South Brazil, the partial or total substitution of native species has been suggested. This study aimed at determining the concentration of crude protein (CP) and in vitro organic matter digestibility (IVOMD) of thirty-eight accessions of exotic and native forage species, accompanied for a period of three years, with or without fertilization. The exotic grasses did not prove superior to the native accessions. The fertilization affected positively the quality parameters, with the accessions showing improved (P < 0.05) CP and IVOMD levels as a result of fertilization. Group formation was not possible as a function of different characteristics of forages, with accessions showing higher levels of CP but lower IVOMD. Paspalum jesuiticum made up a group, recording CP content higher than 15% in contrast to IVOMD lower than 53%. On the other hand, Brachiaria accessions showed IVOMD higher than 60% and CP content lower than 12%. The nutritional parameters involving CP and IVOMD, recorded by exotic accessions, were not enough to justify partial or total substitution of native species found in the pastures of Itajaí Valley.